Fake goods, real money:The counterfeiting business and its financial management - Andrews, Mike (2018)
The trade in counterfeit goods is growing and is increasingly linked to transnational organised crime. But little is known about the financial mechanisms that lie behind this trade. This is the first account of the financial management of the counterfeiting business. Written by experts in a wide range of fields, it examines the financial and business structures in relation to the illicit trade in counterfeit products. Based on interviews with active criminal entrepreneurs in the UK and abroad and other data, the authors explore ‘organised crime’ and mutating criminal markets, digital technologies and their criminological and sociological implications, and cultural values and practices. This book will make a significant contribution to our understanding of these timely issues